PERAN SAYURAN INDIGENOUS DALAM KETAHANAN PANGAN RUMAH TANGGA DI INDONESIA - Kartika Yurlisa (Universitas Islam Kadiri, 2016)
Indigenous vegetable is a native vegetable to the area which has been cultivated and consumed since ancient time or introduction vegetable that has developed and known by people in a particular area. Indigenous vegetables are important source of food and nutrition in Indonesia. However, so far the attention to indigenous vegetables is still lacking, and tend to be abandoned. Micronutrient deficiencies, especially in children, continue to be a global cause for concern and yet numerous reports have revealed the high nutritional value of indigenous vegetables. If they are incorporated into the diet, indigenous vegetables can alleviate some of the micronutrient deficiency concerns. Objective of this paper is to reveal potential role of indigenous vegetables in household food security. In this paper, literature on ethnobotanical knowledge of indigenous vegetables in Indonesia is reviewed. The outcome of the literature search revealed only some plant species of thirty four provinces. In Indonesia the cultivation of these indigenous vegetables has so far been limited. These important vegetables are received less attention although they potentially have a big role to play in food security. Indigenous vegetables need to given more attention so that they can play their role in food security. More work needs to be done to document these important vegetables in all the provinces of Indonesia to create an updated inventory. If these species continue to be neglected and underappreciated, knowledge about them may soon be lost in time and never be recovered.